Antes o mundo não existia: o livro da outra origem do mundo - Lima, Carlos Emílio Barreto Corrêa (2018)
A new way of thinking about old concepts which are transformed almost completely under the influence coming from the energy tought-field flowing from the first literary work written by brazilian indians authors, the cosmogony Antes o mundo não existia, the dessana writers Umúsin Panlõn Kumu and Tolamân Kenhíri (1980 e 1995), a masterpiece of mythical ritual poetry coming from the Amazon Notheast cultural area. This book seems to change almost everything in the field of Literary Theory .Writing, text, literary genders, language, authorship, symbols, myth, sign, poetry, music, ritual, History, religion, science, people traditions, superstitions, unconsciosness, arquetypes, perfomance, midia, narrative structures, receiving the emanations from this “book”, all of these concepts may be changed almost completely in a new configuration. All of them start ,ressounding in a new methamorfical shape, under the power of a unexpectable new conceptual approaching. Landscape, song, chant, places, surroundings, natural enviroment, territory and land are the new keys of a newfound poetical theory. Geography, hydrography is the new text which is magically transformed by this literature.